2017
DOI: 10.1007/s10072-017-2952-3
|View full text |Cite
|
Sign up to set email alerts
|

The atrophy and laterality of the hippocampal subfields in parents with or without posttraumatic stress disorder who lost their only child in China

Abstract: Investigating hippocampal subfields may provide new and important insights into the pathophysiology of posttraumatic stress disorder (PTSD). However, no study has examined the hippocampal subfield volume changes in parents with or without PTSD who had lost their only child and could no longer conceive in China. Fifty-seven parents with PTSD (PTSD+), 11 trauma-exposed parents without PTSD (PTSD-), and 39 non-traumatized controls were recruited to examine the hippocampal subfield volumes using magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…Our results supported the notion that a smaller hippocampus is more likely to be caused by traumatic events than by PTSD itself, and a smaller hippocampus does not appear to be a preexisting risk factor for developing PTSD due to the following reasons: (a) although the volume of the hippocampus is smaller in PTSD patients when compared with HCs, this pattern was also observed in TCs, suggesting trauma contributes to volume reduction; (b) even in the hippocampal body and presubiculum, the only subfields where PTSD‐specific abnormalities were observed, the volumes of these subfields were larger in the PTSD group when compared with TCs (see discussion below: PTSD‐specific Alterations). This result is in line with some previous studies that compared recent‐onset PTSD patients with TCs (Luo et al, 2017; Winter & Irle, 2004), but not all of them (Gilbertson et al, 2002; Zhang et al, 2011). The sample size and heterogeneity of stressors could account for these discrepancies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results supported the notion that a smaller hippocampus is more likely to be caused by traumatic events than by PTSD itself, and a smaller hippocampus does not appear to be a preexisting risk factor for developing PTSD due to the following reasons: (a) although the volume of the hippocampus is smaller in PTSD patients when compared with HCs, this pattern was also observed in TCs, suggesting trauma contributes to volume reduction; (b) even in the hippocampal body and presubiculum, the only subfields where PTSD‐specific abnormalities were observed, the volumes of these subfields were larger in the PTSD group when compared with TCs (see discussion below: PTSD‐specific Alterations). This result is in line with some previous studies that compared recent‐onset PTSD patients with TCs (Luo et al, 2017; Winter & Irle, 2004), but not all of them (Gilbertson et al, 2002; Zhang et al, 2011). The sample size and heterogeneity of stressors could account for these discrepancies.…”
Section: Discussionsupporting
confidence: 92%
“…One study reported smaller CA1 in PTSD veterans than in TCs. Only one study recruited PTSD, TC, and healthy control (HC) subjects at the same time and compared hippocampal subfield volumes among them (Luo et al, 2017). In that study, no significant differences between patients with PTSD and TCs were found (Luo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, cross‐sectional studies have shown that PTSD is related to reductions in hippocampal volume . Additionally, individuals with psychosocial trauma showed reduced hippocampal volume . One longitudinal study showed that stressful life events reduced the volume of gray matter in the hippocampus in as little as 3 months .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that the effects of stress vary across subdivisions of the hippocampus due to their unique functional and cytoarchitectural properties (35). Indeed, previous studies reported smaller volumes in subregions of the cornu ammonis (CA), CA1 (36) and CA3 (37,38), dentate gyrus (DG) (26,37), subiculum (37), and hippocampal-amygdalatransition-area (HATA) (39,40) of PTSD patients compared to controls. Hence, hippocampal volume differences in PTSD may be driven by effects in specific subregions that inform the signature of traumatic stress in the hippocampus and corresponding clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%